Influence of Perioperative Hemodynamic Instability and Glycemic Control on Postoperative Complications in Patients Undergoing Major Abdominal Surgery - Neelam Noreen, Farhana, Wajiha Tabassum, Khan Muhammad Yaqub, Mumtaz Lakho, Mobasher Ahmad Saeed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Major abdominal surgeries are physiologically demanding and frequently associated with perioperative hemodynamic fluctuations and glycemic disturbances. Both hypotension and hyperglycemia have been independently linked to poor surgical outcomes. However, their combined impact on postoperative complications remains underexplored, particularly in resource-limited settings. Objective: To evaluate the influence of perioperative hemodynamic instability and glycemic control on the incidence and severity of postoperative complications in patients undergoing major abdominal surgeries. Methods: This prospective observational study was conducted from June 2022 to May 2023 at Prime Teaching Hospital, Peshawar, and Combined Military Hospital (CMH), Rawalpindi. A total of 100 adult patients undergoing elective major abdominal surgeries were enrolled. Intraoperative hemodynamic instability was defined as a sustained mean arterial pressure (MAP) <65 mmHg for more than 10 minutes. Hyperglycemia was defined as any blood glucose level >180 mg/dL in the perioperative period. Postoperative complications were monitored for 30 days and included surgical site infections, delayed wound healing, ICU admission, acute kidney injury, and prolonged hospital stay. Results: Hemodynamic instability occurred in 31% of patients and perioperative hyperglycemia in 44%. Postoperative complications were significantly higher in patients with hypotension (80.6%) compared to those without (24.6%; p < 0.001), and in hyperglycemic patients (68.2%) compared to normoglycemic patients (21.4%; p < 0.001). The most common complications were surgical site infections (24%), delayed wound healing (18%), and ICU admission (16%). Dual presence of hypotension and hyperglycemia was associated with the highest complication burden. Conclusion: Perioperative hemodynamic instability and hyperglycemia are strong, independent predictors of postoperative complications in major abdominal surgery. Early recognition and management of these modifiable parameters are critical to improving surgical outcomes, especially in high-risk and resource-constrained environments. Keywords: Hemodynamic instability, hyperglycemia, abdominal surgery, postoperative complications, mean arterial pressure, surgical site infection